PENINGKATAN MINAT BELAJAR IMAN KEPADA QADHA DAN QADAR MELALUI STRATEGI PEMBELAJARAN MAKE A MATCH - Hardianti Hardianti (Adiba Aisha Amira, 2024)
This study aims to enhance students' interest in learning about faith in Qadha and Qadar through the application of the Make a Match learning strategy in Grade VI at SDN 13 Batu Manjulur. This Classroom Action Research (CAR) was conducted in three cycles, each consisting of planning, implementation, observation, and reflection stages. The results indicated a significant increase in students' interest and learning outcomes after implementing the Make a Match strategy. This strategy not only made the learning process more engaging but also improved students' active participation and understanding of the material.